PENDAMPINGAN PEMBELAJARAN KOSA KATA MENGGUNAKAN METODE MENYANYI PADA ANAK USIA PRA SEKOLAH DI TPA AR-ROHMAH - Wijaya, Mualim; Jennah, Lailatul; Rahma, Fadilatur; Hikmah, Faiqotul; Sa’diyah, Halimatus (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service program aims to increase understanding and knowledge of Arabic vocabulary through singing and provide innovation to teachers in the application of Arabic learning media at TPA ar-rohmah in Karanganyar village, Paiton district, Probolinggo district. Activities are carried out using several methods such as singing while playing and singing using movement and singing using learning media. The benefits of this activity are; (1) Through singing delivered using the playing method, namely singing with movement, preschool age children can easily recognize Arabic vocabularies, (2) Preschool age children have a high interest in knowing Arabic. This can be seen from the enthusiasm of the children when singing Arabic songs that are taught, and (3) The contents of the short songs and the language used are easy so that students can easily digest and pronounce Arabic vocabulary.